2022
DOI: 10.1177/09567976211055375
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory Content Is Distorted by Its Use in Perceptual Comparisons

Abstract: Visual information around us is rarely static. To perform a task in such a dynamic environment, we often have to compare current visual input with our working memory (WM) representation of the immediate past. However, little is known about what happens to a WM representation when it is compared with perceptual input. To test this, we asked young adults ( N = 170 total in three experiments) to compare a new visual input with a WM representation prior to reporting the WM representation. We found that the percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(56 citation statements)
references
References 37 publications
9
42
0
Order By: Relevance
“… Cicchini, Mikellidou, & Burr, 2018 ) and may reflect the representational integration process to sharpen the precision of the memory representation (e.g. Fukuda, Pereira, Saito, Tang, Tsubomi & Bae, 2022 ). However, given the structure of our paradigm, we are unable to adjudicate whether the influence was from the memorandum or the congruent discriminandum.…”
Section: Methodsmentioning
confidence: 99%
“… Cicchini, Mikellidou, & Burr, 2018 ) and may reflect the representational integration process to sharpen the precision of the memory representation (e.g. Fukuda, Pereira, Saito, Tang, Tsubomi & Bae, 2022 ). However, given the structure of our paradigm, we are unable to adjudicate whether the influence was from the memorandum or the congruent discriminandum.…”
Section: Methodsmentioning
confidence: 99%
“…It has been a lingering question how to separate perceptual interference from other memory errors in participants’ memory reports. Our development of the signal intrusion model, together with some recent modeling work (Dubé et al, 2014; Fukuda et al, 2022; Rademaker et al, 2015; Sun et al, 2017) have provided tentative solutions for this question, with different assumptions of mechanisms underlying the perceptual interference effect. Specifically, research that used revised mixture models (Rademaker et al, 2015; Sun et al, 2017) to separate memory biases, swap errors, and guesses implicitly assumed that perceptual distractions have multiple separable effects on memory reports.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, research that used revised mixture models (Rademaker et al, 2015;Sun et al, 2017) to separate memory biases, swap errors, and guesses implicitly assumed that perceptual distractions have multiple separable effects on memory reports. In contrast, research that used signal integration or averaging models (Dubé et al, 2014;Fukuda et al, 2022) such as our signal intrusion model assumed that the perceptual interference effect is driven by a unified mechanism of intermingling the target signal with the distractor signal during memory reports. Based on this assumption, swap errors and biases are simply caused by differences in the distractor signal strength.…”
Section: Prioritization Effect On Perceptual Interference 13mentioning
confidence: 98%
“…However, recent findings have suggested that performing perceptual comparisons can invoke the updating of a VWM, even if doing so is not desired. Specifically, when asked to evaluate the perceptual similarity between a VWM item and a perceptual probe drawn from the same feature space, subsequent reports of the VWM item were systematically biased towards the perceptual probe, especially when the probe was perceived as similar (Fukuda et al, 2022).…”
Section: Judgments During Perceptual Comparisons Predict Distinct For...mentioning
confidence: 99%
“…Here, we hypothesized that these distinct forms of memory updating may depend on the judgments made during perceptual comparisons. Specifically, we predicted that perceiving similarity between a VWM and novel input would induce integration (Fukuda et al, 2022;, but that perceiving sameness would induce memory replacement. While perceived similarity and dissimilarity reflect separate discretized states along a continuum of representational overlap, they both imply the detection of differences between one's memory representation and their perceptual representation of the novel input.…”
Section: Judgments During Perceptual Comparisons Predict Distinct For...mentioning
confidence: 99%